Hållning av kaniner (Oryctolagus cuniculus) och kaniners beteende i zoobutiker : En inblick i kaninhållning, kaniners beteende samt välfärd i två inhysningssystem i svenska zoobutiker - Segerlund, Linn (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
Rabbits are the fourth most popular pet in Sweden. There are however some concerns about their welfare as companion animals. Pet stores are an important source of knowledge and influence, and they can have a key role in improving rabbit welfare. How pet stores in Sweden house their rabbits, how the housing systems affect rabbit behaviour and implications on rabbit welfare in pet stores are though so far unknown. This study therefore aimed to look at two different housing systems being used in Swedish pet stores, namely rabbit cages and open-top pens. After viewing through literature, sending out a survey and doing behavioural observations some conclusions were made. Cages, especially unenriched, limit the rabbits’ behavioural expression. Social housing is preferred, but there can be complications if the rabbits are housed in small cages, whereby bigger areas are required. The most common housing system in pet stores were however small regular cages, which can therefore be an implication of non-optimal welfare. The behavioural observations complemented that, as the rabbits in the cages were more passive and foraged less than the penned rabbits, but this can be due to differences in age and housing routines. There were, however, bigger behavioural differences between single-housed and group-housed rabbits in cages compared to pens, which can indicate that bigger, open-top pens better meet the behavioural needs of rabbits in pet stores. More studies are however needed to conclude this matter.